Unraveling Hypodesmus Cook, 1896: A preliminary taxonomic revision of the neotropical genus (Polydesmida, Chelodesmidae, Trachelodesmini) - Romero-Rincon, Juan; Martínez-Torres, Daniela; García-Sarmiento, Martha J. (Zootaxa, 2026)
A taxonomic revision of the millipede genus Hypodesmus Cook, 1896 is presented. Female syntypes of the type species, Hypodesmus constrictus (Peters, 1865), are examined and designated as lectotype and paralectotypes. Based on newly collected material, the male is described for the first time, allowing for the generic diagnosis to be confirmed and amended. Type material of Hypodesmus broelemanni Hoffman, 1975 is revised and photographed, and a new record is provided based on recent specimens. Hypodesmus orbiculatus sp. nov. is described from Parque Natural Chicaque, and distribution maps are presented for the genus and for the other members of Trachelodesmini. Finally, additional unidentified material of Trachelodesmini is listed from two Colombian collections.